2020
DOI: 10.3389/fnins.2020.00477
|View full text |Cite
|
Sign up to set email alerts
|

A New Statistical Framework for Corpus Callosum Sub-Region Characterization Based on LBP Texture in Patients With Parkinsonian Disorders: A Pilot Study

Abstract: The study is conducted to identify the best corpus callosum (CC) sub-region that corresponds to highest callosal tissue alteration occurred due to Parkinsonism. In this regard the efficacy of local binary pattern (LBP) based texture analysis (TA) of CC is performed to quantify the changes in topographical distribution of callosal fiber connected to different regions of cortex. The extent of highest texture alteration in CC is used for differential diagnosis. Materials and Methods: Study included subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The findings in PSP, however, were beyond these PD-associated alterations, since in PSP patients, the introduction of a combined parameter score led to a comprehensive textural/microstructural data analysis which showed alterations in frontal CC areas, most prominent in the callosal area II which were significant in comparison to PD patients. The more prominent CC alterations in PSP are in a line of agreement with the findings of a pilot study employing binary pattern-based texture analysis in both disorders which described more localized tissue alterations in mid-callosal regions in PSP (Bhattacharya et al, 2020). Our findings are also in a line of agreement with a fixelbased study in patients with neurodegenerative parkinsonism which demonstrated a reduction of a combined measure of fiber density and cross-section in the body of the CC in PSP (Nguyen et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…The findings in PSP, however, were beyond these PD-associated alterations, since in PSP patients, the introduction of a combined parameter score led to a comprehensive textural/microstructural data analysis which showed alterations in frontal CC areas, most prominent in the callosal area II which were significant in comparison to PD patients. The more prominent CC alterations in PSP are in a line of agreement with the findings of a pilot study employing binary pattern-based texture analysis in both disorders which described more localized tissue alterations in mid-callosal regions in PSP (Bhattacharya et al, 2020). Our findings are also in a line of agreement with a fixelbased study in patients with neurodegenerative parkinsonism which demonstrated a reduction of a combined measure of fiber density and cross-section in the body of the CC in PSP (Nguyen et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…The Tamura texture [16] analysis method is effective to analyze the contrast, coarseness and directionality of the image, but it is poor in recognition of the linelikeness, regularity and roughness of the image. The algorithm of extracting texture feature based on Gabor [17] wavelet transform has better retrieval effect in frequency domain, and it can eliminate redundant information. But the higher the dimension of feature vector increases, the more slowly the retrieval speed becomes.…”
Section: A Shortcoming Of Extracting Texture Algorithmsmentioning
confidence: 99%
“…3 Figure 4. In addition, the texture of flaws on the product surface is very similar to the background texture, so it is very difficult to extract feature of flaws by the extracting texture algorithm [17,18]. The defective product could not be identified, as shown in Sect.…”
Section: Bdescription Of the Proposed Algorithmmentioning
confidence: 99%